Randomized controlled trial of cognitive remediation therapy in adolescent inpatients with anorexia nervosa: Neuropsychological outcomes. (23rd May 2022) - Herbrich‐Bowe, Laura; Bentz, Lea K.; Correll, Christoph U.; Kappel, Viola; van Noort, Betteke M.
Abstract: Objective: Neuropsychological dysfunction exists in anorexia nervosa (AN). Cognitive Remediation Therapy (CRT), mainly evaluated in adults with AN, targets these impairments. Methods: Adolescent inpatients (age = 11–17 years) with AN were randomized to 5 weeks of either 10 sessions of individually delivered CRT or non‐specific cognitive‐training (NSCT). Co‐primary outcomes included cognitive domain 'flexibility' [composite score of Wisconsin Card Sorting Test (WSCT) and Trail Making Test (TMT‐4)] and 'central coherence' [composite score of Central Coherence Index (CCI) and Group Embedded Figures Test (GEFT)] at end of treatment (FU1). Secondary outcomes included individual test scores and self‐reported everyday‐life flexibility at FU1 and at 6‐months post‐treatment (FU2). Independent sample t ‐tests, Pearson chi‐square‐tests and mixed models for repeated measures (MMRM) analyses were conducted. Results: In 56 females (age = 15.1 ± 1.5 years), CRT was not superior to NSCT at FU1 regarding 'flexibility' ( p = 0.768) or 'central coherence' ( p = 0.354), nor at FU2 ( p = 0.507; p = 0.624) (effect sizes = 0.02–0.26). Both groups improved over time in central coherence (CCI p = 0.001; GEFT p < 0.001), self‐reported flexibility ( p = 0.002) and WCST ( p = 0.18), but not TMT‐4 ( p = 0.286). NSCT was superior to CRT regarding self‐reported planning/organisation ability at FU1 ( p < 0.001) and FU2 ( p = 0.003). Conclusions: CRT was not superior to NSCT in adolescent inpatients with AN. More randomized controlled studies are needed. Key points: This randomized controlled trial (RCT) of Cognitive Remediation Therapy (CRT) in adolescent inpatients with anorexia nervosa (AN) indicates no superiority of CRT compared to a non‐specific cognitive training (NSCT) with regard to cognitive flexibility, central coherence and self‐reported everyday‐life functions. The findings suggest that comparable studies in adults with AN with a longer duration of illness cannot be directly applied to adolescent populations with AN. More research is needed into outcomes that best capture CRT effects in adolescents including randomized controlled trials further investigating motivational aspects, metacognitive abilities and behavioural changes related to the eating disorder as well as everyday coping skills in this age group.